Seeking blessings of the elders - Mumbai Archive Project Team (Jio Institute, 2024)
Before the haldi (turmeric) ceremony, members of the family, clan and community seek blessings from the bride and the groom by touching their feet. Similarly, the bride and the groom also seek blessing from elders in the family, clan and community by touching their feet.